Book Review: The Healthy Love and Money Way: How the Four Attachment Styles Impact Your Financial Well-Being - Renee L. Earwood; Brandon D. Ratzlaff (Journal of Financial Therapy, 2021)
Book Review: The Healthy Love and Money Way: How the Four Attachment Styles Impact Your Financial Well-Being